Research Progress of DUB Enzyme in Hepatocellular Carcinoma - Zhao, Jie; Guo, Jinhui; Wang, Yanan; Ma, Qiancheng; Shi, Yu; Cheng, Feng; Lu, Qiliang; Fu, Wen; Ouyang, Guangxiong; Zhang, Ji; Xu, Qiuran; Hu, Xiaoge (Frontiers in Oncology, 2022)
Abstract According to GLOBOCAN 2021 cancer incidence and mortality statistics compiled by the International Agency for Research on Cancer, hepatocellular carcinoma (HCC) is the most common malignancy in the human liver and one of the leading causes of cancer death worldwide(1). Although there have been great advances in the treatment of liver cancer, such as regofenib, sorafenib, and lomvatinib, which have been developed and approved for the clinical treatment of advanced or metastatic HCC. However, they only prolong survival by a few months(2), and patients with advanced liver cancer are susceptible to tumor invasion metastasis and drug resistance (3). Ubiquitination modification is a type of post-translational modification of proteins. It can affect the physiological activity of cells by regulating the localization, stability and activity of proteins , such as: gene transcription, DNA damage signaling and other pathways (4). The reversible process of ubiquitination is called de-ubiquitination (5): it is the process of re-releasing ubiquitinated substrates with the participation of de-ubiquitinases (DUBs) and other active substances. There is growing evidence that many dysregulations of DUBs are associated with tumorigenesis (6). Although dysregulation of deuquitinase function is often found in liver cancer and other cancers, the mechanism of action of many deuquitinases and hepatocellular carcinoma has not been elucidated. In this review, we focused on several deubiquitinases (DUBs) associated with hepatocellular carcinoma, including their structure, function, and relationship to hepatocellular carcinoma. The mechanism of action of "OTUB1, OTUD3, USP14, USP10, USP39, UCH37" in hepatocellular carcinoma was highlighted, as well as the latest research reports. In addition, we discussed the prospects and significance of targeting DUBs as a new strategy for the treatment of hepatocellular carcinoma.